Discussion on Application of Cardioid to Horizontal Arch Ring of Arch Dam - ZHOU Bin (Renmin Zhujiang)
In recent years,arch ring types of arch dam tend to be diversified.Some scholars put forward the cardioid as the horizontal arch ring of arch dam.However,the stress characteristics of the cardioid are not fully considered when the arch ring is arranged,so there are certain defects.It is of great significance to further study the nature of the cardioid and optimize the arrangement of the cardioid arch ring for the development of arch dam design technology.This paper finds out some basic properties for cardioid as the horizontal arch ring through mathematical derivation,proposes a new type of cardioid arch ring arrangement with considering the stress characteristics,and calculates the stress of the dam surface by the multi-arch beam method based on the shape of a similar arch dam with cardioid in an existing project.The results show that the stress of the new arch dam is not much different from that of the original arch dam,so it can be preliminarily judged that the use of the cardioid in the shape design of arch dam is feasible,which can be considered as a supplement to the common ring types of arch dam and further verified by the engineering.